An industrial scale process for the enzymatic removal of steryl glucosides from biodiesel. Issue 1 (December 2015) - Peiru, Salvador; Aguirre, Andres; Eberhardt, Florencia; Braia, Mauricio; Cabrera, Rodolfo; Menzella, Hugo
Abstract Background Biodiesels produced from transesterification of vegetable oils have a major quality problem due to the presence of precipitates, which need to be removed to avoid clogging of filters and engine failures. These precipitates have been reported to be mostly composed of steryl glucosides (SGs), but so far industrial cost-effective methods to remove these compounds are not available. Here we describe a novel method for the efficient removal of SGs from biodiesel, based on the hydrolytic activity of a thermostable β-glycosidase obtained fromThermococcus litoralis . Results A steryl glucosidase (SGase) enzyme fromT. litoralis was produced and purified fromEscherichia coli cultures expressing a synthetic gene, and used to treat soybean-derived biodiesel. Several optimization steps allowed for the selection of optimal reaction conditions to finally provide a simple and efficient process for the removal of SGs from crude biodiesel. The resulting biodiesel displayed filterability properties similar to distilled biodiesel according to the total contamination (TC), the cold soak filtration test (CSFT), filter blocking tendency (FBT), and cold soak filter blocking tendency (CSFBT) tests. The process was successfully scaled up to a 20 ton reactor, confirming its adaptability to industrial settings. Conclusions The results presented in this work provide a novel path for the removal of steryl glucosides from biodiesel using a cost-effective, environmentally friendly and scalable enzymatic process, contributing to the adoption of this renewable fuel.